THE ROLE OF FAMILY SUPPORT IN IMMUNIZATION OF MEASLES RUBELLA IN ELEMENTARY SCHOOL AGE CHILDREN - Sunarto Kadir (Universitas Negeri Gorontalo, 2021)
Measles is an acute disease that is easily transmitted and is one of the top five causes of under-five mortality in Indonesia, while rubella is a very dangerous disease if it infects pregnant women and causes congenital disease in babies born. Measles rubella (MR) immunization so that it affects family support (parents) in carrying out the immunization in elementary school-aged children. This research was conducted on children in Elementary Schools in Batudaa District, Gorontalo District. The research objective was to analyze family support in implementing MR immunization in elementary school age children. This type of research is descriptive quantitative. The population was all parents of grade 1 elementary school students in Batudaa Subdistrict, Gorontalo District, totaling 221 people, while the total sample was 176 people using accidental sampling technique. Data were analyzed descriptively and presented in the form of frequency distribution and percentage tables. The results showed that family support (parents) for the implementation of MR immunization in grade 1 SD students in Batudaa District was 89.8%, while those who were not supported were 10.2%. Thus the coverage of MR immunization has been said to be good and it is hoped that it can be maintained and increased by optimizing the socialization related to the importance of MR immunization in the working area of the Batudaa Community Health Center.